Supply Chain Management Practices Of Road Construction Firms In Ghana - Kyei, Philip Kwasi (2015)
A Thesis Submitted to the Department of Building Technology, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the award of a degree of Master of Science in Construction Management, 2014